2004
DOI: 10.1103/physrevb.69.214511
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo study of the pairing symmetry competition in the Hubbard model

Abstract: To shed light into the pairing mechanism of possible spin-triplet superconductors (TMTSF)2X and Sr2RuO4, we study the competition among various spin singlet and triplet pairing channels in the Hubbard model by calculating the pairing interaction vertex using the ground state quantum Monte Carlo technique. We model (TMTSF)2X by a quarter-filled quasi-one dimensional (quasi-1D) Hubbard model, and the γ band of Sr2RuO4 by a two dimensional (2D) Hubbard model with a band filling of ∼ 4/3. For the quasi-1D system, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
5
24
0
Order By: Relevance
“…The result is consistent with Ref. [22], where d Now we move on to the extended Hubbard model in Fig.2, where the DCA+QMC result for the pairing susceptibility is plotted as a function of the off-site interaction V for T = 0.125 with the Trotter-Suzuki decomposition number L = 24. We can clearly see a qualitative tendency that p x+y and d xy become dominant with the introduction of V , while p x and d x 2 −y 2 are suppressed.…”
supporting
confidence: 88%
“…The result is consistent with Ref. [22], where d Now we move on to the extended Hubbard model in Fig.2, where the DCA+QMC result for the pairing susceptibility is plotted as a function of the off-site interaction V for T = 0.125 with the Trotter-Suzuki decomposition number L = 24. We can clearly see a qualitative tendency that p x+y and d xy become dominant with the introduction of V , while p x and d x 2 −y 2 are suppressed.…”
supporting
confidence: 88%
“…164 Namely, d xy is more favored when the dimerization is weaker, t b /t c is closer to unity (closer to isotropic triangular lattice), and the Fermi surface splitting is larger. These factors strongly depend on the anions.…”
Section: Studies For the Hubbard Model On The Original Four Band Latticementioning
confidence: 99%
“…140) because the nodes of the d xy gap do not intersect the Fermi surface, but the T c problem still exists even in that case. 164 In fact, Kondo and Moriya have studied the four band model using FLEX, and showed that a realistic T c can be obtained only when the dimerization is extremely strong (|t b1 /t b2 | > 5). 165 Such a strong dimerization indeed contradicts with the extended Hückel 119, 120 or the first principles calculations, 166,167 and also leads to the d x 2 −y 2 -wave pairing, which is not in agreement at least with the thermal conductivity 144 and the STM experiments 143 for X=Cu(NCS) 2 .…”
Section: Studies For the Hubbard Model On The Original Four Band Latticementioning
confidence: 99%
“…This triggered interest in low-dimensional models of correlated electrons showing mechanism for Cooper pairing of triplet symmetry coexisting or closely competing with SDW type ordering. Although a wide variety of theoretical approaches have so far been used to study this topic [23,24,25,26,27,28,29], the understanding of the microscopic mechanisms for the complex phenomena in these compounds is still far from complete.…”
Section: Introductionmentioning
confidence: 99%